Transcriptional and clonal characterization of B cell plasmablast diversity following primary and secondary natural DENV infection - Adam T. Waickman; Gregory D. Gromowski; Wiriya Rutvisuttinunt; Tao Li; Hayden Siegfried; Kaitlin Victor; Caitlin Kuklis; Methee Gomootsukavadee; Michael K. McCracken; Benjamin Gabriel; Anuja Mathew; Ariadna Grinyo i Escuer; et al. (My University, 2020)
Antibody-mediated humoral immunity is thought to play a central role in mediating the immunopathogenesis of acute DENV infection, but limited data are available on the diversity, specificity, and functionality of the antibody response at the molecular level elicited by primary or secondary DENV infection. In order to close this functional gap in our understanding of DENV-specific humoral immunity, we utilized high-throughput single cell RNA sequencing to investigate B cells circulating in both primary and secondary natural DENV infections. We captured full-length paired immunoglobulin receptor sequence data from 9,027 B cells from a total of 6 subjects, including 2,717 plasmablasts. In addition to IgG and IgM class-switched cells, we unexpectedly found a high proportion of the DENV-elicited plasmablasts expressing IgA, principally in individuals with primary DENV infections. These IgA class-switched cells were extensively hypermutated even in individuals with a serologically confirmed primary DENV infection. Utilizing a combination of conventional biochemical assays and high-throughput shotgun mutagenesis, we determined that DENV-reactive IgA class-switched antibodies represent a significant fraction of DENV-reactive Igs generated in response to DENV infection, and that they exhibit a comparable epitope specificity to DENV-reactive IgG antibodies. These results provide insight into the molecular-level diversity of DENV-elicited humoral immunity and identify a heretofore unappreciated IgA plasmablast response to DENV infection.
Keywords: Humoral immunity; Immunoglobulin M; T-cell and B-cell Immunology